Potentials of Endophytes of Andrographis Paniculata for the Production of Plant Growth Promoters, Enzymes and Antimicrobial Compounds (SAARC Journal of Agriculture, 2022)
In the present study, 9 bacterial and 6 fungal endophytes were isolated from surface sterilized leaf, stem and root samples of the medicinal plant - Andrographis paniculata (Kalmegh). The endophytes were screened for plant growth promoting traits (IAA, phosphate solubilization and N2 fixation), enzymes (cellulase and amylase) and antimicrobial compounds against 3 potent human pathogens- E. coli, Staphylococcus sp. and Vibrio sp. The majority of the isolated endophytes produced the phytohormone - IAA (ranging 2-45μg/ml), and 1 endophyte solubilized phosphate and fixed N2. All the fungal endophytes possessed cellulase and amylase activity. In the preliminary screening, 4 bacterial and 4 fungal endophytic isolates extract showed antagonistic activity against the 3 potent human pathogens which are known causative agents of urinary tract, skin and gastrointestinal tract infections, respectively. The endophytes of A. paniculata exhibiting broad and specific antimicrobial activity make them ideal candidates in medical purposes.SAARC J. Agric., 19(2): 157-170 (2021)